2020
DOI: 10.1161/circulationaha.119.044127
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Oxidative Injury With Targeted Expression of NADPH Oxidase 2 Short Hairpin RNA Prevents Onset and Maintenance of Electrical Remodeling in the Canine Atrium

Abstract: Background: Atrial fibrillation (AF) is the most common heart rhythm disorder in adults and a major cause of stroke. Unfortunately, current treatments of AF are suboptimal because they are not targeted to the molecular mechanisms underlying AF. Using a highly novel gene therapy approach in a canine, rapid atrial pacing model of AF, we demonstrate that NADPH oxidase 2 (NOX2) generated oxidative injury causes upregulation of a constitutively active form of acetylcholine-dependent K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Potentiation of mitochondrial free radical scavenging mechanisms induced by overexpression of catalase in transgenic mice was sufficient to prevent mitochondrial dysmorphology, SR Ca 2+ leak and inducibility of AF [ 45 ]. Attenuation of oxidative stress by the silencing of the NADPH oxidase 2 with a gene-based approach successfully prevented the electrical remodeling of atrial myocardium and maintenance of the arrhythmia in a canine model of AF [ 64 ], and gene therapy directed at the improvement of mitochondrial antioxidative capacity may also be effective in prevention of AF.…”
Section: Involvement Of Mitochondrial Dysfunction In the Pathogenesis Of Afmentioning
confidence: 99%
“…Potentiation of mitochondrial free radical scavenging mechanisms induced by overexpression of catalase in transgenic mice was sufficient to prevent mitochondrial dysmorphology, SR Ca 2+ leak and inducibility of AF [ 45 ]. Attenuation of oxidative stress by the silencing of the NADPH oxidase 2 with a gene-based approach successfully prevented the electrical remodeling of atrial myocardium and maintenance of the arrhythmia in a canine model of AF [ 64 ], and gene therapy directed at the improvement of mitochondrial antioxidative capacity may also be effective in prevention of AF.…”
Section: Involvement Of Mitochondrial Dysfunction In the Pathogenesis Of Afmentioning
confidence: 99%
“…Likewise, Kim et al showed that NADPH-driven ROS production, reflective of NADPH activity, was significantly increased in the right atrial appendage in patients with postoperative AF [85]. Interestingly, NADPH-driven ROS production underlies the onset and maintenance of electrical remodeling in AF, which can be successfully prevented with a novel gene-based approach which inhibits NADPH-driven ROS production in AF models [86]. Generation of ROS levels that exceed the detoxification capacity of the cell leads to impaired mitochondrial function through oxidative damage of DNA, proteins, and lipids [87,88].…”
Section: Mitochondrial Nad + Depletion Confers Cardiomyocyte Dysfunction In Afmentioning
confidence: 99%
“…Injection and electroporation of plasmids expressing shRNA against NOX2 in the atrium of a canine AF model not only delayed the time to onset of nonsustained AF more than fivefold but also prevented the development of sustained AF for up to 12 weeks. 113…”
Section: Inflammation/oxidative Injurymentioning
confidence: 99%
“…We showed that oxidative injury contributes to electrical remodeling in AF by upregulating a constitutively active form of acetylcholine‐dependent K + current ( I KAch )—called I KH —by a mechanism involving frequency‐dependent activation of protein kinase C epsilon (PKC ε ). Injection and electroporation of plasmids expressing shRNA against NOX2 in the atrium of a canine AF model not only delayed the time to onset of nonsustained AF more than fivefold but also prevented the development of sustained AF for up to 12 weeks 113 …”
Section: Targets For Gene Therapymentioning
confidence: 99%